United Kingdom : Financial Sector Assessment Program-Fund Management and Equity Trading Platforms: Regulation, Supervision, and Systemic Risk Monitoring-Technical Note. (IMF Staff Country Reports; Country Report ;, 2016)
This paper reviews the effectiveness of the regulation, supervision, and systemic risk monitoring of investment funds and their managers. The United Kingdom has the largest fund management market in Europe and a key role as the host for some of the most important European equity trading platforms. A significant proportion of the regulatory framework in this area, in particular that related to conduct of business and disclosure requirements, has been harmonized at the EU level and is largely in line with the relevant international standards. The Financial Conduct Authority has the primary responsibility for the regulation and supervision of fund management and equity trading platforms.